Monitoring thermic patterns in beehives via wireless sensor networks - Douglas Santiago Kridi (2014)
Swarming is the mass exodus of bees in a hive, whose most common causes are lack of food, stress, variations of humidity and especially high temperatures. Among the types of swarming, one in which the complete abandonment of the hive occurs has brought great harm to Brazilian beekeepers, particularly the Northeast. In the Northeast region, of great importance for the Brazilian beekeeping, and where high temperatures are common in most of the year, a large number of hives is lost due to the swarming through abandonment. In an attempt to mitigate this problem, we propose a proactive monitoring hives via a network of wireless sensors capable of identifying atypical heating indicative of a preswarming condition. By means of a sampling pattern obtained from the cyclical daily temperatures, we developed a predictive algorithm based on pattern recognition techniques capable of detecting the increase of temperature inside the beehive (microclimate) responsible for the typical stress bees culminating in swarming. Such a mechanism is also able to recognize and avoid sending redundant information over the network in order to reduce radio communication, thereby reducing costs of data transmission and energy.